The Efficiency of Electrocoagulation and Electroflotation Processes for Removal of Polyvinyl Acetate From Synthetic Effluent - Zeinab Atashzaban; Abdolmotaleb Seidmohammadi; Davood Nematollahi; Ghasem Azarian; Omid Heidary Shayesteh; Ali Reza Rahmani (Hamadan University of Medical Sciences, 2016)
Polyvinyl acetate (PVAc) is a type of thermoplastic resin generated by a polymerization of vinyl acetate. Effluent of this polymer is highly rich with chemical oxygen demand (COD) and total solids (TS). Due to lack of studies on the above problem, the current study aimed at obtaining a sufficient method for the effluent pre-treatment. In fact, the study discussed PVAC effluent treatment by electrocoagulation (EC) and electroflotation processes.The study considered the effect of various operating parameters such as pH and current density, initial concentration of pollutant, inter-electrode distance, electrolysis times, and types of electrode materials (iron and aluminum); COD and TS removal efficiency and optimal values of operational parameters were calculated. In the study, COD and TS reduction rates in the optimized conditions in batch flow reactor were 83% and 78%, and 80% and 72% for Fe and Al electrodes, respectively. Optimized conditions were taken as 24 mA cm -2, 20 g/L PVAC, and neutral pH in 20 minutes for Al-Al electrodes and 15 minutes for Fe-Fe electrodes, 1 cm distance between electrodes with parallel-type monopole of connection modes. According to the results, electrochemical process with batch flow tends to be a suitable pre-treatment process that is inexpensive, easily operated, and highly sufficient for effluent treatment, which contains polyvinyl acetate.